Aberrant Alternative Polyadenylation is Responsible for Survivin Up-regulation in Ovarian Cancer - Xiang-Jun He; Qi Zhang; Li-Ping Ma; Na Li; Xiao-Hong Chang; Yu-Jun Zhang (Chinese Medical Journal, 2016)
Background: Survivin is an oncoprotein silenced in normal mature tissues but reactivated in serous ovarian cancer (SOC). Although transcriptional activation is assumed for its overexpression, the long 3'-untranslated region (3'-UTR) in survivin gene, which contains many alternate polyadenylation (APA) sites, implies a propensity for posttranscriptional control and therefore was the aim of our study. Methods: The abundance of the coding region, the proximal and the distal region of survivin mRNA 3'-UTR, was evaluated by real-time polymerase chain reaction (PCR) in SOC samples, cell lines, and normal fallopian tube (NFT) tissues. The APA sites were confirmed by rapid amplification of cDNA 3' ends and DNA sequencing. Real-time PCR were used to screen survivin-targeting microRNAs (miRNAs) that were inversely correlated with survivin. The expression of an inversely correlated miRNA was restored by pre-miRNA transfection or induction with a genotoxic agent to test its inhibitory effect on survivin overexpression. Results: Varying degrees of APA were observed in SOC by comparing the abundance of the proximal and the distal region of survivin 3'-UTR, and changes of 3'-UTR correlated significantly with survivin expression (r = 0.708, P< 0.01). The main APA sites are proved at 1197 and 1673 of survivin 3'-UTR by DNA sequencing. Higher level of 3'-UTR proximal region than coding region was observed in NFT, as well as in SOC and cell lines. Among the survivin-targeting miRNAs, only a few highly expressed miRNAs were inversely correlated with survivin levels, and they mainly targeted the distal part of the 3'-UTR. However, in ovarian cancer cells, restoration of an inversely correlated miRNA (miR-34c) showed little effect on survivin expression. Conclusions: In NFT tissues, survivin is not transcriptionally silenced but regulate posttranscriptionally. In SOC, aberrant APA leads to the shortening of survivin 3'-UTR which enables it to escape the negative regulation of miRNAs and is responsible for survivin up-regulation.